(untitled) (Società e diritti, 2022)
Abstract The last initiative of the European Union reform, Macron’s proposal, later assumed by Germany, and by the Commission and the European Parliament, seeks to build a federal, sovereign, and autonomous European Union in the international arena. Born in 2017, in a context of crisis of confidence in the EU, driven by the Covid-19 pandemic, it has been incorporated into the European agenda. The debates of the Conference on European reform, which began in May 2021 and ended in June 2022, it has been conditioned by the War in Ukraine, the relaunch of NATO and the relative weakness of the executives of the states of the Union. But overall, the most important drawback to advancing politically in the EU is found in the non-existence of a European citizenship identified with a federal Europe and the inability of the EU to stop being a club of states and establish direct alliances and identity complicities with non-elitist sectors of European citizenship. The lack of capacity of the Commission and Parliament to incorporate the defense of the rights and opportunities of linguistic minorities, above the states, is a good example of why the European institutions do not have solid strategies to create a European demos and a diverse and plural European identity that could be both supra-state and sub-state.